Labor Regulation and Employment in India's Retail Stores - Amin, Mohammad (2012)
A new dataset of 1,948 retail stores in India shows that 27% of the stores find labor regulations as a problem for their business. Using these data, we analyze the effect of labor regulations on employment at the store level. We find that flexible labor regulations have a strong positive effect on job creation. Our estimates show that labor reforms are likely to increase employment by 22% of the current level for an average store. We also address the issue of informality in India's retail sector. Our findings suggest that more flexible labor laws can encourage firms to operate in the more efficient formal retail sector. According to our estimates, labor reforms could reduce the level of informality by as much as 33%.